DEVELOPMENT AND IN VITRO EVALUATION OF SOLID DISPERSIONS OF CANDESARTAN CILEXETIL - KUMAR, UPPULURU ASHOK; SURESH, GANDE (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective The main objective of the present study is systematic development of solid dispersions of Candesartan cilexetil by solvent evaporation method to enhance the solubility and bioavailability. Methods In the present study, eighteen formulations of solid dispersions were prepared with 1:1 and 1:3 ratios of drug: carrier and with and without surfactant. There was significant improvement in the rate of drug release from all 20 solid dispersions and the formulation (SD16) comprising Candesartan: containing Soluplus (1:3 ratio of drug:Â  Soluplus with 2% SLS as surfactant) by solvent evaporation process. Results Final optimized design SD16 contained maximum drug content of 99.08%. In in vitro dissolution studies it shows greater dissolution rate i.e. 99.7Â±4.2% associated through additional designs and pure drug. The drug was compatible with all the excipients as per FTIR (Fourier transform infrared spectroscopy). From powder X-ray diffraction (p-XRD) and by (SEM) studies it was evident that crystalline form of Candesartan has been converted into amorphous form within solid dispersion design. Conclusion From these studies we can accomplish solid dispersions are one of the greatest favorable formulation for Candesartan cilexetil for enhancing the solubility and bioavailability of poorly water soluble drugs in the effective group of hypertension and other cardiac problems.